Bebidas Alcoólicas: uma abordagem CTS no contexto de ensino remoto de Química - (:unkn) unknown (Universidade Federal do Pampa, 2020)
It is possible to identify different views about the thematic that involves alcoholic beverages, because at the same time that they are classified as licit drugs, causing a high number of deaths annually in the global sphere, they also play a significant role in the profits of the industries and trade of distilled and fermented drinks, in addition to being part of the intrinsic culture of most societies, being popularly found in events and celebrations. Therefore, it appears that this scientific-social theme has two sides, that is, there are different ways to interpret it, making it suitable for teaching using the STS approach (acronym for Science, Technology and Society) according to Santos apud Ramsey (2008). This is a way of verifying that economic, cultural and technological development are directly intertwined, enabling students to reflect on a controversial topic that is part of their daily lives. In view of this, the present work refers to a case study that has as its general objective: to problematize and discuss, based on a remote teaching intervention, the theme of alcoholic beverages in the STS scope for a General Chemistry class of the Degree in Chemistry from a public institution of Higher Education. The work was based on three main stages: 1) Definition of the study focus, 2) Data collection and 3) Systematic analysis of the data and aimed to address a problem-situation involving the production and consumption of alcoholic beverages during 4 remote encounters. The results obtained from the intervention demonstrated that the practice was significant in order to encourage the search and construction of arguments by the students who participated, insofar as they were willing to devise solutions and work in teams in an attempt to remedy the problematic proposal. Noting thus, the internalization of chemical knowledge and manifestation of critical thinking in the speeches, which involved scientific technological, social and environmental issues regarding the theme of alcoholic beverages.
Keywords: CTS; Bebidas alcoólicas; Situação-problema; Alcoholic Beverages; Problem-situation; CNPQ::CIENCIAS EXATAS E DA TERRA